Science and technology in Ecuador: First approach to its current status at national level - Salazar-Mera, Juan Eduardo (2019)
The objective of the research was to analyze the technological activity in the Ecuadorian context, by offering a first approach to this type of business from a conceptual and empirical point of view. A documentary review was performed at general level related to information technologies’ conceptualization and in detail about the policies and regulations applied to the Ecuadorian case. It also analyzed the expenditure on science and technology activities and the use of information and communication technologies at the enterprise level. The data is based on the Ecuadorian Institute of Statistics and Censuses (INEC) surveys corresponding to 2009-2015. According to the analysis, provisional conclusions were drawn on the current role of activities related to science and information technology and their possible contribution to the diversification of scientific and technological activity of Ecuador.